Sex determination by osteometric assessment of the mastoid process using Cone Beam Computed Tomography - Salemi, Fatemeh; Farhadian, Maryam; Shokri, Abbas; Safi, Yaser; Rahimpanah, Shahin (Brazilian Dental Science, 2020)
Objective: Sex determination is one of the most important parameters to identify in forensic science. Because the mastoid process is the most resistant to damage due to its position in the skull base, it can be used for sex determination. The purpose of this study was to measure the dimensions and convexity and internal angles of the mastoid process to present a model of sex determination in Iranian population. Material and methods: This study was performed on three-dimensional images of 190 Cone Beam Computed Tomography (CBCT) of 105 women and 85 men. On each CBCT the distance between the porion and the mastoid (PM), mastoid length (ML), the distance between the mastoidale and the mastoid incision (M-I), the mastoid height (MH), the mastoid width (MW), intermastoidale distance (IMD) the lateral surfaces of the left and right mastoids (IMLSD) and the Mastoid medial convergence angle (MMCA) was measured on both the right and the left. The data were analyzed by descriptive statistics, t-test, and discriminant function analysis. Results: Significant differences were found for all variables except MMCA and MF in both sex. All measured variables except MW were greater for men than women. The discriminant model achieved a total accuracy of 93.7%. Among the measured factors IMD and IMSLD had the most influence on sex determination. Conclusion: Measuring the dimensions of the mastoid process is a very good method for sex determination with high accuracy of 90%. KEYWORDS Discriminant model; Cone beam computed tomography (CBCT); Sex determination; Mastoid process.